WACANA HADIS DALAM MANHAJ NAHDLATUL ULAMA` - Fikri Hamdani (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
This simple article describes the discourse of Hadith in the manhaj of Nahdlatul Ulama. This discussion is descriptive-analytical study focused on NU's view of the hadith of the Prophet. In its development, the clerical view of hadith is very diverse, it is due to the approach and methodology used are different from each other. NU is one of the largest Islamic organizations in Indonesia, also has its own perspective in understanding the hadith of the Prophet. For example about the criteria of hadith accepted or rejected, both in terms of status or position of hadith and the practice of a hadith. This discussion is very interesting to be studied more deeply, because this is very closely related to the legal istinbath of Nahdlatul Ulama which is contained in Bahtsul Masa'il.